2011
DOI: 10.1038/cmi.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin directly interacts with Toll-like receptor 4 and suppresses lipopolysaccharide-induced inflammatory cytokine secretion from THP-1 cells

Abstract: Mannan-binding lectin (MBL) plays a key role in the lectin pathway of complement activation and can influence cytokine expression. Toll-like receptor 4 (TLR4) is expressed extensively and has been demonstrated to be involved in lipopolysaccharide (LPS)-induced signaling. We first sought to determine whether MBL exposure could modulate LPS-induced inflammatory cytokine secretion and nuclear factor-kB (NF-kB) activity by using the monocytoid cell line THP-1. We then investigated the possible mechanisms underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 60 publications
9
56
0
Order By: Relevance
“…The results of ELISA assay verified the decrease of IL-8 and CXCL1 in CRC cells treated with sTLR4/MD-2 complex (Figure 4C). These results of pro-inflammatory and migration cytokines were consistent with previous studies [37, 38]. Since these pro-inflammatory and migration cytokines constituted tumor microenvironment of CRC to affect tumor progression [18], it was suggested in our study that sTLR4/MD-2 complex can inhibit tumor progress (Figure 5A) whereas sTLR4 or MD-2 alone could not inhibit tumor progress as effectively as sTLR4/MD-2 complex.…”
Section: Discussionsupporting
confidence: 92%
“…The results of ELISA assay verified the decrease of IL-8 and CXCL1 in CRC cells treated with sTLR4/MD-2 complex (Figure 4C). These results of pro-inflammatory and migration cytokines were consistent with previous studies [37, 38]. Since these pro-inflammatory and migration cytokines constituted tumor microenvironment of CRC to affect tumor progression [18], it was suggested in our study that sTLR4/MD-2 complex can inhibit tumor progress (Figure 5A) whereas sTLR4 or MD-2 alone could not inhibit tumor progress as effectively as sTLR4/MD-2 complex.…”
Section: Discussionsupporting
confidence: 92%
“…[33] recently showed that recombinant MBL could interact with TLR4 and MD-2. More recently, we proved that MBL could bind to TLR4 directly, and suppress LPS-/TLR-mediated biological function [22]. The finding of an inhibitory effect of MBL on C. albicans -induced immune responses of human macrophages through TLR2 and TLR4 in this study further demonstrated the versatile ability in immune regulation of this member of the collectin family.…”
Section: Discussionsupporting
confidence: 67%
“…We have proved that MBL could bind to TLR4 directly, and suppress LPS-/TLR-mediated biological function [22]. TLR4 is the binding site (ligand) for MBL expressed on THP-1 cells.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The vast majority of studies indicate that MBL inhibits proinflammatory cytokine production (24,25,(38)(39)(40). Contradicting results, however, depending on the level of recombinant MBL or the experimental setup used, have been published (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%